Application of Molecular Vapour Deposited Al2O3 for Graphene-Based Biosensor Passivation and Improvements in Graphene Device Homogeneity - Muhammad Munem Ali; Jacob John Mitchell; Gregory Burwell; Klaudia Rejnhard; Cerys Anne Jenkins; Ehsaneh Daghigh Ahmadi; Sanjiv Sharma; Owen James Guy (Nanomaterials, 2021)
Graphene-based point-of-care (PoC) and chemical sensors can be fabricated using photolithographic processes at wafer-scale. However, these approaches are known to leave polymer residues on the graphene surface, which are difficult to remove completely. In addition, graphene growth and transfer processes can introduce defects into the graphene layer. Both defects and resist contamination can affect the homogeneity of graphene-based PoC sensors, leading to inconsistent device performance and unreliable sensing. Sensor reliability is also affected by the harsh chemical environments used for chemical functionalisation of graphene PoC sensors, which can degrade parts of the sensor device. Therefore, a reliable, wafer-scale method of passivation, which isolates the graphene from the rest of the device, protecting the less robust device features from any aggressive chemicals, must be devised. This work covers the application of molecular vapour deposition technology to create a dielectric passivation film that protects graphene-based biosensing devices from harsh chemicals. We utilise a previously reported “healing effect” of Al2O3 on graphene to reduce photoresist residue from the graphene surface and reduce the prevalence of graphene defects to improve graphene device homogeneity. The improvement in device consistency allows for more reliable, homogeneous graphene devices, that can be fabricated at wafer-scale for sensing and biosensing applications.